Development of Hashimoto's disease in patients with vitiligo - Jakub Paprocki; Anna Mataczyńska; Michał Paprocki; Mateusz Dobosz; Klaudia Arciszewska; Anna Szpernalowska; Vimbisoyashe Ivy Matshaba; Karolina Mrugała; Martyna Choinka; Jakub Kalisiak (Nicolaus Copernicus University in Toruń, 2024)
The aim of this paper is to review the available scientific literature on the relationship between vitiligo and the development of Hashimoto's disease, with particular emphasis on possible pathogenetic mechanisms and clinical implications of this correlation. The relationship between vitiligo and thyroid diseases, especially Hashimoto's disease, has intrigued researchers for years. Numerous clinical observations suggested that patients with vitiligo more often struggle with thyroid problems, but only extensive epidemiological studies allowed for a precise estimate of the scale of this phenomenon.